2018
DOI: 10.1002/ldr.2965
|View full text |Cite
|
Sign up to set email alerts
|

Mortierella elongata's roles in organic agriculture and crop growth promotion in a mineral soil

Abstract: The addition of organic amendments contributes substantially to improvements in soil quality and prevents soil degradation. However, very little is known about the responses of dominant fungal strains to organic fertilizers or their functions in the nutrient transformations and crop growth promotion. Here, soils and maize roots were collected from a 35‐year field experiment treated with composted soybean cake. The fungal communities in the bulk soil, rhizosphere, and endosphere were analyzed by deep amplicon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 65 publications
12
87
0
Order By: Relevance
“…Since both plowing and manuring had been performed between the spring and summer sampling events, it is not possible to determine whether the effects on fungal communities observed were due to seasonal changes, tillage, or manure addition. Considering the potential importance of Mortierella in breaking down complex carbon sources, promoting plant growth, and improving soil health [44][45][46] , further exploration of factors influencing Mortierella growth in agricultural soils should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Since both plowing and manuring had been performed between the spring and summer sampling events, it is not possible to determine whether the effects on fungal communities observed were due to seasonal changes, tillage, or manure addition. Considering the potential importance of Mortierella in breaking down complex carbon sources, promoting plant growth, and improving soil health [44][45][46] , further exploration of factors influencing Mortierella growth in agricultural soils should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Li et al . () found that a closely related species ( M. elongata ) can improve soil health and stimulate production of plant growth hormones. In their study, Chung et al .…”
Section: Discussionmentioning
confidence: 99%
“…We found one cluster of ASV taxonomically assigned to Mortierella (soil saprotrophs) positively correlated to productivity in both tomato and pepper roots. Interestingly, Li et al (2018) found that a closely related species (M. elongata) can improve soil health and stimulate production of plant growth hormones. In their study, Chung et al (2007) showed how increases in productivity led to greater microbial biomass and greater number of saprophytic and arbuscular mycorrhizal fungi.…”
Section: Discussionmentioning
confidence: 99%
“…We found Mortierella was the most abundant genus in this study (Table S3), and this genus was classified as undefined saprotrophic fungi using FUNGuild. The genus Mortierella comprises a diverse group of soil‐dwelling saprobes (Li et al, ), and members of this genus are known to assist crops and mycorrhizal fungi in phosphorus acquisition (Osorio & Habte, 2014; Tamayo‐Velez & Osorio, ) and have the ability to decompose plant litter and degrade aromatic hydrocarbons (Ellegaard‐Jensen, Aamand, Kragelund, Johnsen, & Rosendahl, ; Osono, ). In a previous study, the abundance of Mortierella was found to be significantly increased in the rhizospheric soils of soybean that had been CC for 2 and 3 years (Bai et al, ).…”
Section: Discussionmentioning
confidence: 99%